Cost Efficient Synthesis of Diaryl Ethers Catalysed by CuI, Imidazolium Chloride and Cs2CO3. Issue 24 (24th June 2019) - Paul, Sudeep; Joy, Bony P.; Rajendran, Rajarajan; Gudimetla, Vittal B.
Abstract: Synthetically versatile imidazolium chlorides, especially 1, 3‐bis‐(2, 6‐diisopropylphenyl)‐imidazolium chloride (IPrHCl) along with copper (I) iodide and cesium carbonate, were found to be useful to form C−O bonds via coupling of phenols and aryl/heteroaryl bromides. In this catalysis, the metal:ligand (Cu:IPr) loading was optimised to 1.0 mol%, making it an inexpensive and a simple one pot catalytic route for synthesising a variety of diaryl ethers. The catalytic cycle was probed by UV‐Vis, FT‐IR and HRMS techniques confirming involvement of a copper‐imidazolium‐carbonate complex. Abstract : CuI, IPrHCl and Cs2 CO3 based Ullmann C−O cross‐coupling reaction is developed. The reported procedure introduces a cost efficient route for the synthesis of diaryl ethers using an easily scalable ligand precursor (IPrHCl) with low catalyst loading (1.0 mol %) and under ambient reaction conditions. The catalytic cycle of the reaction was studied using FT‐IR, UV‐Vis absorption spectroscopy and HRMS techniques.